Quality of work life: a study of multinational corporations in Malaysia - Lau, Yeng Wai; Chung, Wand Chih; Ng, Siew Imm (Inderscience, 2022)
Believed to help improve productivity and commitment to the workplace, work-life balance and quality of work life are widely studied issues of interest. Much is still to be learned about how best to improve workplace wellness especially with the increasing need to work beyond office hours, not to mention family demands and other challenges in life. This study contributes by examining the extent to which supervisor support can enhance quality of work life at multinational corporations in Malaysia via a questionnaire survey. Results suggest that supervisor support enhances quality of work life, which in turn, motivates organisational commitment and improves quality of life. Such findings suggest the importance of educating supervisors, especially expatriates, of what constitutes supportive supervisor behaviour and essence of a satisfying experience at work that inspire organisational commitment and improve overall life satisfaction.